Assessing the Effect of an Ethnomathematics Teaching Material on Students’ Understanding of Mathematics - Linda Vitoria; Monawati; Fauzi; Mislinawati (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
The integration of cultural context in mathematics teaching materials is a form of implementing ethnomathematics-based teaching. It is an effort of making mathematics learning easier and meaningful. This paper reports the effect of an ethnomathematics teaching material on students’ understanding of linear equations at the Department of Primary Education Universitas Syiah Kuala. 105 students participated in the study. Students’ understanding was assessed using a test. Data analysis was conducted using descriptive qualitative method. Students’ understanding of linear equation was analyzed based on 3 aspects of solving linear equation problems: correctly translate word problems into linear equation, perform calculation correctly, and give correct final answer. Results showed that more than 83% of the students could answer the test satisfactorily. Therefore, it is concluded that the implementation of the ethnomathematics teaching material helps students understand linear equation. This finding implies that the implementation of ethnomathematics teaching material is beneficial for mathematics learning.